2015
DOI: 10.5750/ejpch.v3i3.984
|View full text |Cite
|
Sign up to set email alerts
|

Equity and person-centeredness in provision of tinnitus services in UK National Health Service audiology departments

Abstract: Rationale, aim and objective: Chronic tinnitus is a prevalent condition broadly managed using individualised sound-based interventions, individualised or group education, counselling, or cognitive therapies. In the UK, therapy is largely delivered by audiologists or hearing therapists and, where available, clinical psychologists and physicians. Changes in the structure of the health service necessitate ongoing evaluation to monitor equity and person-centeredness of care. The purpose of the current evaluation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…In a survey of English National Health Service audiology departments, 65% of clinicians indicated that they were not able to refer outside of their service to a clinical psychologist or other health professional qualified in providing psychological therapy (Gander et al, 2011). In a more recent evaluation of audiology services in the four countries of the UK, only services in England reported ever having a clinical psychologist in their team (7%) and access to a member of staff trained in CBT (48%), with a third of all services offering CBT as part of standard care (37%; Hoare et al, 2015). Self-help interventions can provide a way of improving access to psychological services for tinnitus.…”
Section: Actmentioning
confidence: 99%
“…In a survey of English National Health Service audiology departments, 65% of clinicians indicated that they were not able to refer outside of their service to a clinical psychologist or other health professional qualified in providing psychological therapy (Gander et al, 2011). In a more recent evaluation of audiology services in the four countries of the UK, only services in England reported ever having a clinical psychologist in their team (7%) and access to a member of staff trained in CBT (48%), with a third of all services offering CBT as part of standard care (37%; Hoare et al, 2015). Self-help interventions can provide a way of improving access to psychological services for tinnitus.…”
Section: Actmentioning
confidence: 99%
“…A further concern regarding tinnitus management in the United Kingdom is that many who experience tinnitus remain without access to tinnitus treatment, as they are not always referred for treatment by their general practitioner (El-Shunnar et al, 2011). For those who are referred, both the structure and provision of tinnitus services throughout the United Kingdom is variable, leading to inequality in tinnitus care (Hoare et al, 2015). Cognitive behavioral therapy (CBT), a psychological intervention aimed at altering maladaptive responses to tinnitus through behavioral modifications, has the most evidence of effectiveness at reducing tinnitus distress (Hesser et al, 2011).…”
mentioning
confidence: 99%
“…Although a recent British Tinnitus Association tinnitus service evaluation showed that 74% of UK audiology clinics can offer combination hearing aids (Hoare et al, 2015), the challenges that we faced in recruiting existing combination device users suggests that the numbers of wearers are small. Recruitment into a UK clinical trial would need to enrol either existing conventional hearing aid (amplification only) users or those who do not use any devices to manage their hearing loss and tinnitus.…”
Section: Discussionmentioning
confidence: 98%